2021
DOI: 10.1136/bcr-2020-240601
|View full text |Cite
|
Sign up to set email alerts
|

TARP syndrome associated with renal malformation and optic nerve atrophy

Abstract: Talipes equinovarus, atrial septal defect, Robin sequence and persistent left superior vena cava (TARP) syndrome is a congenital disease caused by mutations in the RBBM10 gene. It has a low prevalence and a high rate of mortality in the neonatal stage. In this case report, we present a case of a 32-week gestational age preterm newborn with a prenatal diagnosis of intrauterine growth restriction, with a persistent left superior vena cava, interatrial communication and a horseshoe kidney. Additionally, postnatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Another peculiar thing about our case was the coexistence of the persistent left SVC (PLSVC) with polycystic kidney disease. Careful literature review regarding the occurrence of renal anomalies with persistent left SVC revealed multiple cases of horseshoe kidney [12,13], unilateral absent kidney [14], and crossed fused ectopic kidney [15]. Co-occurrence of multicystic dysplastic kidney with PLSVC was reported four times: a case of familial 22q11.2 deletion syndrome [16], a case of complete trisomy 9 [17], a case of 17q12 deletion [18], and a case of polyalanine expansion mutation of ZIC3 gene [19].…”
Section: Discussionmentioning
confidence: 99%
“…Another peculiar thing about our case was the coexistence of the persistent left SVC (PLSVC) with polycystic kidney disease. Careful literature review regarding the occurrence of renal anomalies with persistent left SVC revealed multiple cases of horseshoe kidney [12,13], unilateral absent kidney [14], and crossed fused ectopic kidney [15]. Co-occurrence of multicystic dysplastic kidney with PLSVC was reported four times: a case of familial 22q11.2 deletion syndrome [16], a case of complete trisomy 9 [17], a case of 17q12 deletion [18], and a case of polyalanine expansion mutation of ZIC3 gene [19].…”
Section: Discussionmentioning
confidence: 99%
“…30 where caused by mutations in the RBM10 gene. 35 Several cases reported that, the patient had physical findings in common but more patients are identified through genetic testing. The TARP syndrome acronym was widened into more complex cardiac lesions, distal limb defect in combine with TEV, disfunction of nervous system and renal abnormalities.…”
Section: Vacterl Associated Anomaliesmentioning
confidence: 99%